Composite timber-steel encased columns subjected to concentric loading. (1st April 2021) - Kia, L.; Valipour, H.R.
Highlights: Hybrid timber-steel encased columns are proposed and experimentally evaluated. Hybridising timber column with encased steel rod significantly enhance the strength. CoV of strength of hybrid timber-steel columns is smaller than bare timber columns. Analytical model for estimating strength of hybrid timber-steel column is proposed. Abstract: Novel composite timber-steel encased columns were proposed to fully exploit advantages and address short-comings of timber and steel; two construction materials with different mechanical properties and complementary benefits. The encased steel bars were adhesively bonded inside the timber casing to achieve near full composite action. The load carrying capacity, failure mechanisms, stiffness, and ductility of 48 hybrid members under concentric axial compression were experimentally evaluated and compared with bare timber columns, where the benefits of hybridising timber with steel bars are highlighted. The composite columns were designed with intermediate slenderness and varying steel core area, steel grade (300PLUS, 5.8, N500 and 8.8), timber species (Radiata Pine and Douglas fir) and timber grade (MGP10 and F5). When compared to bare timber columns, the proposed composite columns demonstrated increased axial capacity, stiffness, and ductility. Analytical expressions based on principles of structural mechanics and existing design provisions are developed to estimate the stiffness and strength of the composite columns. Non-contact Digital Image Correlation (DIC) was employed to measure strain and predict crack initiation. The practical benefits of composite timber-steel encased columns are also discussed, notably the potential to express the materiality of wood and offer a market for low-grade timber with smaller cross sections.